Pelatihan Desain User Interface (UI) Berbasis Praktik untuk Meningkatkan Kompetensi Siswa DKV SMK Bhakti Nusantara Kabupaten Demak - Muslih Muslih; Noor Hasyim; Henry Bastian; Abi Senoprabowo; Ali Muqoddas; Elkaf Rahmawan P.; Novia Wahyu W. (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2026)
User Interface and User Experience (UI/UX) design training is an important effort to enhance the competencies of vocational high school (SMK) students, particularly those in the Visual Communication Design (DKV) program, in order to align with the demands of the digital industry. This activity aims to develop students’ skills in designing web-based application interfaces through training using Figma and Adobe XD. The method applied is project-based learning, which includes the delivery of fundamental UI/UX concepts, wireframing, interface design, and the development of interactive prototypes. The participants of this activity were DKV students at SMK Bhakti Nusantara Mranggen.The results of the training indicate an improvement in students’ understanding of UI/UX concepts as well as their ability to produce more structured and user-oriented designs. Students were also able to utilize key features in Figma and Adobe XD to create interactive interface designs and prototypes. In addition, there was a shift in students’ workflow from static graphic design using Adobe Photoshop and CorelDRAW toward a system-based and user experience–oriented design approach. Therefore, this training contributes to improving students’ readiness to meet the demands of the digital creative industry.